The coronavirus conundrum – Part III - Pacheco-Romero, José (2020)
The new coronavirus pandemic continues with us and will do so for a long time. It has brought a new way of life, with isolation, confinement, personal protection, distancing, use of virtuality and others. The diagnosis of the infected and its management has been improved; there is no cure yet, although there are vaccines approved in haste. The health crisis has exposed the lack of preparation of our health systems, resulting in political and economic crises, with impoverishment, death, and emotional and psychological complications. In these pages we continue writing in a summarized way the new knowledge about SARS-CoV-2 and the COVID-19 disease, its diagnosis, pathophysiology, symptomatic management and the severe disease, re-infection, its sequelae and lethality. But mainly how it affects the infected woman during pregnancy, childbirth and the puerperium, as well as aspects of rooming in and breastfeeding. And what happens when the infection affects the newborn. The future of the mothers and children who suffered the infection remains to be known.